Establishment of Ship Allocation Model by Using Marine Logistics Database (MLDB) - Mohammad Danil Arifin; Fanny Octaviani (Institut Teknologi Sepuluh Nopember, 2022)
Recently, marine big data are significantly increased. If the data are effectively analyzed, it can give an advantage, and we can harness the data that is useful for a decision-maker in maritime industries. The Marine Logistics Database (MLDB) was successfully developed in the previous studies. It was developed by integrating big data into a relational database. By utilizing the extracted data from the developed database (DB), the model of ship allocation will be established. In this study, the main purpose is to develop a ship allocation model that matches the results with the existing ship allocation. In this study, the effectiveness of the allocation model was examined by checking the port constraints, ship specification, and allocation process itself. Moreover, some simulations were executed and discussed to develop new ship allocation and analyze the effective ship specification.